Development of Augmented Reality-Based Chemistry Learning Media Integrated with Local Wisdom on Colloid System Material to Reduce Misconceptions and Improve Learning Outcomes - Freddy Tua Musa Panggabean; Astriana Purba; Hotma Br. Butar Butar; Mei Sufi Anisa Sibarani; Monalisa Situmorang; Rina Syadilla; Vanessa Putri Rizky Simanullang; Yoren Valentina Br. Tarigan (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Chemistry education on colloid systems presents persistent challenges due to the abstract and submicroscopic nature of the concepts involved, which conventional instructional methods struggle to address effectively. This study aimed to develop Augmented Reality (AR)-based chemistry learning media integrated with local wisdom for colloid system instruction, evaluate its validity and practicality, and measure its effectiveness in reducing misconceptions and improving students' learning outcomes. Using the ADDIE development model with a one-group pretest-posttest design, the study was conducted at SMA Swasta Methodist 7 Medan involving 26 students of class XI IPA. The developed media consisted of two AR marker-based learning tools: AR Link 1 covering dispersed substances, dispersion media, and colloid types contextualized through local cultural examples such as gulai and teh talua, and AR Link 2 visualizing colloid properties including Brownian motion, the Tyndall effect, coagulation, dialysis, adsorption, and electrophoresis through animated microscopic representations. Validation results showed average scores of 4.4 (content) and 4.3 (language) categorized as valid, and a perfect score of 5 (very valid) across all media aspects. The instrument validation reached 93.1%, categorized as highly feasible. Student learning interest ranged from good to very good (74.04%–80%), and observation data confirmed active participation (75%–95%). The N-gain score of 0.64 indicated moderate improvement in conceptual understanding, while posttest results demonstrated substantial reduction of misconceptions across all colloid concepts. The AR-based media integrated with local wisdom was concluded to be valid, practical, and effective for colloid system learning.